The study on karyotypes of five Grylloidea species (Orthoptera: Grylloidea) in Northeast China - You, Ju-Xia; Li, Na; Ren, Bing-Zhong; Yuan, Hai-Bin; Shang, Li-Na (Zootaxa, 2007)
The karyotypes of five Grylloidea species from Jilin province in northeast China were studied. A clustering analysis of their chromosomal relative lengths was studied for the first. In the males, chromosome numbers vary from 2n = 27 (%) to 2n = 19 (%) and Fundamental Numbers (FN) from 30 to 19. All the species have the basic Orthopteran sex determining mechanism XX&/X0%. The results of clustering analysis showed that the five species form two well-supported groups with a Rescaled Distance of 15: (1) the genus Gryllodes and Teleogryllus and (2) the genus Oecanthus. In particular, the morphologically close species of G. supplicans and G. sigillatus, T. emma and T. occipitalis are strongly supported. The relationships among the five species are as follows: (((G. supplicans, G. sigillatus), (T. emma, T. occipitalis)), O. longicauda).